Cryophotonics: Experimental Validation of a SOA Model Down to Cryogenic Temperatures - Maeva Franco; Lydia Kacel; Edwin Fontenelle; Pascal Morel; Thierry Rampone; Arnaud Gardelein; Ammar Sharaiha (IEEE Photonics Journal, 2025)
Cryophotonics is a promising way of boosting state-of-the-art photonic components using cryogenic temperatures. In this work, in addition to confirm our experimental results with measurements on another component, we present a theoretical analysis of SOA behavior at cryogenic temperatures. Based on the obtained experimental results, we expand the SOA model range by introducing temperature dependence on the main SOA physical parameters such as band gap energy level, recombination coefficients, internal losses and effective electron and holes masses. The model is applicable over a wide temperature range from ambient down to cryogenic temperatures. A qualitative agreement is found between simulations and experiments. The comparisons are given down to 70 K in terms of gain spectrum, saturation output power and noise figure which demonstrate the effectiveness of the model.